2015
DOI: 10.1016/j.iatssr.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of horizontal and sag vertical curves on two-lane rural roads: Driving simulator study

Abstract: a b s t r a c t a r t i c l e i n f o Available online xxxxThe highway geometric design guidelines for several countries provide suggestions for the coordination of horizontal curves overlapping with sag vertical curves (sag combinations) to avoid combined configurations that produce undesirable optical effects and reduced safety. Such suggestions are derived from studies based on the drawing of the perspective of the road. This drawing method is severely limited with respect to the simulation of the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…20 % of all fatalities being the result of run-off-road accidents, mitigating this hazard becomes a priority. Horizontal curves and their parameters have a strong impact on road safety [24] [29]. Horizontal curves are strictly related to speed and visibility [30].…”
Section: Parameters Of Horizontal Curvesmentioning
confidence: 99%
“…20 % of all fatalities being the result of run-off-road accidents, mitigating this hazard becomes a priority. Horizontal curves and their parameters have a strong impact on road safety [24] [29]. Horizontal curves are strictly related to speed and visibility [30].…”
Section: Parameters Of Horizontal Curvesmentioning
confidence: 99%
“…Wyniki badań tego zagadnienia [1,2,3] sugerują, że bezpieczeństwo związane z poruszaniem się po łukach poziomych wynika z trzech powiązanych ze sobą kwestii: zaburzenie uwagi kierowcy, niedostosowanie prędkości do krzywizny oraz niewystarczająca szerokość pasa jezdni. Kolejnym ważnym czynnikiem uwzględnianym w badaniach jest stan nawierzchni w obrębie łuków poziomych [4].…”
Section: Problem Bezpieczeństwa W Ruchu Drogowym Na łUkach Poziomychunclassified
“…In China, driving simulators are recommended as tools by the country's Specifications for Highway Safety Audit, especially for roads with complex terrain (3). In many studies (4)(5)(6)(7), driving simulators are used to evaluate combined alignments and roadside design safety, and an increasing prevalence of highway design safety evaluation using a driving simulator is observed.…”
mentioning
confidence: 99%
“…The DOF of a motion system is very important for experimental validity. The motion system may influence driver speed (7,8), acceleration (7,9), and lane deviation (10,11). A series of studies investigated the relationship between these driving performance variables and combined alignments using driving simulators (5,7,11), which showed that these variables were vital for highway design safety evaluation.…”
mentioning
confidence: 99%
See 1 more Smart Citation